THE EFFECTIVENESS OF RED BETEL LEAF AND ALOE VERA IN THE TREATMENT OF PERINEAL WOUNDS: LITERATURE REVIEW - Firdaus Mubayyina (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Treatment of perineal wounds in postpartum women can be done by pharmacological and non-pharmacological methods, namely through complementary therapy with the use of herbs, which is betel leaf and aloe vera that have anti-inflammatory, anti-septic, anti-fungal and antibacterial effects. The purpose of this study was to determine the effectiveness of red betel leaf and aloe vera in the treatment of perineal wounds. This study uses a Literature Review, journal searches using Medline, PubMed, Tandfonline and Google Scholar databases for the last ten years. Analysis of the data used is descriptive statistics. Some literature discusses the treatment of perineal wounds using red betel leaf and aloe vera and has been shown to be effective in the perineum wound healing process in post artum mothers with an average length of healing that is faster than treatment without the intervention of red betel leaf and aloe vera. Conclusion, red betel leaf and aloe vera can be applied in the treatment of perineal wounds in postpartum.